ANALISA SUMBER-SUMBER PERTUMBUHAN EKONOMI FILIPINA PERIODE 1994-2003 - SIAGIAN, VICTOR (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 2 Juli 2005)
Economic crisis hit South East Asia countries after depreciation of Thailand’s currency toward US dollar. The indicator of economic crisis reflected by decreasing of economic growth. This research describes empirical phenomenon of economic growth in Philippine, using analysis method, dynamic model “Error Correction Model” (ECM). In the short run, significant contributions toward economic growth in Philippine, caused by foreign investment and domestic debt. In the long run, positive and significant contribution toward economic growth caused by export, import, domestic investment, saving and government expenditure, macroeconomic variables. Positive but not significant contribution caused by foreign investment. Foreign and domestic debt caused negative and not significant toward economic growth. This research can be used as one of references for improving economic growth of Indonesia.
Keywords: Economic Crisis, Economic Growth Phenomenon, Dynamic Model, Error Correction Model (ECM), Macro Economic Variables, Positive and Significant Contribution